ANALYSIS OF DIMENSIONS AND TRENDS IN THE DIGITAL TRANSFORMATION OF CUSTOMS SYSTEMS - RĂCĂTĂIAN RALUCA IOANA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The present study aims to explore the impact of the implementation of information and communication technologies (ICT) in customs administrations, in the context of increasing the efficiency of the management of large volumes of data from various sources. The main objectives of research include assessing how ICT can improve the taxpayer experience and the internal efficiency of administration. The study will also focus on identifying the challenges associated with the lack of specialized workforce and the absence of a globally unified digital strategy in the public sector. A central aspect of the research is the analysis of the opportunities offered by ICT, such as the implementation of the "Single Window" for electronic filing of customs information, which facilitates interoperability between the automated customs systems of the member states of the European Union. In addition, it will investigate how digitization contributes to the effective use of data analysis, from descriptive to prescriptive models, to optimize tax collection and tax compliance. Next, the study will examine the implementation and strengthening of the Customs Integrated Information System (SIIV), which integrates various subsystems and improves data exchange, security and accessibility of information. It will also assess the long-term impact of digital transformation, including the adoption of emerging technologies such as blockchain and artificial intelligence, as well as aligning with the dynamics of changes in global trade, with the aim of effectively supporting international trade and ensuring its security.